2021
DOI: 10.3390/mi12121465
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Compressibility of Cellulose Nanofiber-Stabilized Microdroplets Using Acoustophoresis

Abstract: Droplets with a liquid perfluoropentane core and a cellulose nanofiber shell have the potential to be used as drug carriers in ultrasound-mediated drug delivery. However, it is necessary to understand their mechanical properties to develop ultrasound imaging sequences that enable in vivo imaging of the vaporization process to ensure optimized drug delivery. In this work, the compressibility of droplets stabilized with cellulose nanofibers was estimated using acoustophoresis at three different acoustic pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…Previous studies have shown that CNF-shelled PFP droplets are stabilized via a Pickering mechanism. 11 Figure 2A shows that similarly to the previous work by Ghorbani et al 11 and Loskutova et al, 27 CNFs act as a stabilizing agent as they form a coherent layer on the surface of the droplets. The initial droplet size of the produced emulsion is determined by the energy density, ie, energy dissipated per unit volume of the processed mixture, with an increase in energy output decreasing the size of produced droplets.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Previous studies have shown that CNF-shelled PFP droplets are stabilized via a Pickering mechanism. 11 Figure 2A shows that similarly to the previous work by Ghorbani et al 11 and Loskutova et al, 27 CNFs act as a stabilizing agent as they form a coherent layer on the surface of the droplets. The initial droplet size of the produced emulsion is determined by the energy density, ie, energy dissipated per unit volume of the processed mixture, with an increase in energy output decreasing the size of produced droplets.…”
Section: Discussionsupporting
confidence: 80%
“…The two droplet components that may have a cytotoxic effect is the cationic CNFs and PFP. Previous studies have estimated the volume fraction of CNF to be between 1.5% and 8.8% 27 and the density of CNFs to be 1.5 g/cm 3 . 53 Therefore, the volume of CNF present in 72 droplets should be between 1.68 and 11.21 pL, or between 2.53 and 16.82 ng.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…c HNC Tu686, 686LN, M4e, 37B -head and neck cancer cells whereas M4e & 37B have a higher metastatic potential than Tu686 & 686LN; density and compressibility from Wang et al ). e MESC2.10 -human embryonic ventral mesencephalic cell; MESC2.10-diff4d -human embryonic ventral mesencephalic cell differentiated in a special medium for 4 days; Augustsson et al 21 ; the acoustic contrast Φ is measured via acoustic manipulation at 1.97 MHz; we multiplied the average Φ from 21 by a factor of 3 to match our definition of Φ. f Loskutova et al 31 demonstrated a negative ACF, whereas the ACF is dependent on the pressure amplitude. g SaOs-2 & LM5 -human bone cancer cell line with a lower respectively higher metastatic potential and ACF data generated during this study.…”
Section: /15mentioning
confidence: 99%